Sjögren's Syndrome in Ophthalmology and Dentistry and its correlation with patients' quality of life (Research, Society and Development, 2022)
Sjögren's Syndrome is a chronic autoimmune disorder that mainly affects the epithelium of the lacrimal and salivary glands.,The main clinical characteristics are dry eye (xerophthalmia), dry mouth sensation (xerostomia) and reduced salivary flow. This study aimed to characterize Sjögren's Syndrome, including secondary alterations of concomitant diseases that impact the patient's quality of life, to assess in an interdisciplinary way the sicca manifestations (xerophthalmia and xerostomia), to report the interrelationship of the oral microbiota and the pathogenesis of the syndrome and describe the intraoral and systemic manifestations. To obtain the necessary data, a bibliographic search was carried out in PUBMED databases with the following MeSH descriptors: “Sjögren's Syndrome” and “Dentistry”, these were combined using the Boolean operator "AND" and SCIELO with the keyword "Sjögren's Syndrome”. Only original articles in portuguese, english and spanish were included, considering the period from 2016 to 2022. In total, 655 studies were found, and of these, only 13 were selected for meeting the inclusion criteria. The studies analyzed showed that Sjögren's Syndrome requires a multidisciplinary management, in which the interaction between Rheumatologist and Dentist and Ophthalmologist are extremely important, contributing to early diagnosis, control of signs and symptoms and to promote individualized treatment, providing quality of life for these patients.